2017
DOI: 10.1016/j.conbuildmat.2017.02.110
|View full text |Cite
|
Sign up to set email alerts
|

Railway ballast condition assessment using ground-penetrating radar – An experimental, numerical simulation and modelling development

Abstract: This paper reports on the GPR-based assessment of railway ballast which was progressively "polluted" with a fine-grained silty soil material. It is known how the proper operation of a ballast track bed may be undermined by the presence of fine-grained material which can fill progressively the voids between the ballast aggregates and affect the original strength mechanisms. This occurrence is typically defined as "fouling". To this effect, a square-based methacrylate tank was filled with ballast aggregates in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Some experimental studies have analysed the influence of different fouling levels in the electromagnetic waves. In [35], four different levels were simulated (from 0% to 76% fouling) and two different air-coupled antennas were used with frequencies of 1 GHz and 2 GHz. Regarding the assessment of the moisture content in the ballast, this parameter was easily evaluated by GPR as the dielectric value of the ballast increases with the presence of water [36].…”
Section: Overview On the Use Of Gpr For Railway Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Some experimental studies have analysed the influence of different fouling levels in the electromagnetic waves. In [35], four different levels were simulated (from 0% to 76% fouling) and two different air-coupled antennas were used with frequencies of 1 GHz and 2 GHz. Regarding the assessment of the moisture content in the ballast, this parameter was easily evaluated by GPR as the dielectric value of the ballast increases with the presence of water [36].…”
Section: Overview On the Use Of Gpr For Railway Monitoringmentioning
confidence: 99%
“…The first step was to establish a range, in the time and frequency domains, that corresponds to segments of each acquired trace of the GPR signals that are considered to better reflect the changes in the track condition at subsurface layers level [15,35,40,63].…”
Section: Range Selection Of Gpr Signal In Time and Frequency Domainsmentioning
confidence: 99%
“…Hence, a simulation domain with dimensions complying with the above real‐life conditions is realized. This proves to be effective for model validation purposes (comparison between simulated and measured scenarios) (Benedetto et al., ; Benedetto et al., ), as will be discussed in Section . Nevertheless, if higher resolutions are required for the simulation of the real object (e.g., fine or microscale investigations), it is worth noting that the size and the shape of the elementary components must be reproduced consistently.…”
Section: Methodsmentioning
confidence: 99%
“…The above two approaches have shown some limitations that are discussed in Benedetto et al. (). In more detail, one of the restrictions of the “clump logic” approach is that the model ignores the internal contacts between the overlapping spheres (Ferellec and McDowell, ; Indraratna et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Benedetto et al [12] investigated the response of a rubber mixed ballast which would have low stiffness and the results should increase in vibration in low frequency bands of 10 -30 Hz. Zhang et al [13] found that the increase in thickness, decreases particle velocity.…”
Section: Selected Parametersmentioning
confidence: 99%